Beyond "Leanear" production: A multi-level approach for achieving circularity in a lean manufacturing context. (10th October 2021) - Schmitt, Thomas; Wolf, Christopher; Lennerfors, Thomas Taro; Okwir, Simon
Abstract: Despite the growth of the research on lean and green manufacturing systems, consideration of how circular economy principles complement lean has been virtually absent from the literature due to a mismatch between research on lean green, which has focused on the internal manufacturing operations (product and process levels), and research on the circular economy, which takes a broader, more holistic view of environmental impact (the system level). Only a few researchers have considered the lean and the circular together. We argue that there is a need to understand the complementarities and conflicts between "lean" and "circularity". By combining the system level with process and product levels, this paper highlights which potentials in a lean manufacturing context are identified from a circular perspective and how to realize them. In this paper, we present a critical case study conducted at a Swedish manufacturing firm/original equipment manufacturer within the heavy-duty and off-road (HDOR) industry. Our results show that the company is locked into a lean and linear production, where material waste is not seen as a resource. We present how the three levels interplay and argue that they be combined when trying to integrate circular measures into this context.